A) 4x-(x+6)+4 dla 1/3,
b) (x2+1)-(x2-2)+10 dla 2,2,
c) (a+4b)-(5+2a)-(3b-5) dla a= -0,1 i b= 0,2,
d) (-a2+2ab-1)+(a2-4ab+5) dla a=1/4 i b=2


OBJAŚNIENIE: w przykładzie b (x2+1)-(x2-2) to x do potęgi drugiej
tak samo w przykładzie d (-a2+2ab-1)+(a2-4ab+5) to -a2 i a2 to x do potęgi drugiej

1

Odpowiedzi

2010-01-19T21:55:04+01:00
A) 4x-(x+6)+4=4x-x-6+4=3x+2=3*1/3+2=1+2=3
b) (x2+1)-(x2-2)+10=x2+1-x2+4+10=15
c) (a+4b)-(5+2a)-(3b-5)=a+4b-5-2a-3b+5=-a+b=-(-0,1)+2=2,1
d) (-a2+2ab-1)+(a2-4ab+5)=-a2+2ab-1+a2-4ab+5=-2ab+4=-2(0,25*2)+4=-1+4=3
1 5 1